BERTRAND RUSSELL'IN FELSEFE ANLAYIŞI ÜZERİNE BİR İNCELEME - Fikri Gül (Felsefe Dünyası)
Bertrand Russell, one of the most important thinkers of the twentieth century, has a unique position in philosophy by his opinions and determinations within the framework of his philosophical understanding. He is a member of the "Vienna Circle" and he brought a new perspective to philosophy by his "logical positivist" approach which he called "my own philosophy". According to Russell, who view philosophy with respect to logic and science, it was necessary to apply a new technique to philosophy and this was a mathematical logic and science. On the one hand, he indicates the importance of philosophy as a special discipline. On the other hand, however, he reduces its value by viewing it as a subordinate element of science. In this essay, Russell's own ideas about philosophy are studied systematically, and some critical material the objections that were raised against the opinions held by the thinker is presented.